Changes in Mycobacterium tuberculosis-Specific Immunity With Influenza co-infection at Time of TB Diagnosis - Mendy, Joseph; Jarju, Sheikh; Heslop, Rhiannon; Bojang, Adama L.; Kampmann, Beate; Sutherland, Jayne S. (Frontiers in Immunology, 2019)
Background: Prior Influenza A viral (IAV) infection has been shown to increase susceptibility to tuberculosis (TB) and TB has also been shown to be a primary cause of death during pandemics, including the Spanish Influenza outbreak of 1918-1919. The majority of data has been obtained from mouse models, thus the aim of this study was to determine the impact of Flu co-infection on host immunity and disease severity in TB patients at diagnosis. Methods: Sputum from 282 patients with active TB were analysed for presence of FluA/FluB RNA at presentation using multiplex PCR. Sputum RNA was also analysed for Mycobacterium tuberculosis (Mtb) load using 16S RNA amplification. Supernatants from digested sputum and Mtb antigen-stimulated whole blood were analysed using multiplex cytokine arrays and PBMC were analysed for cytokine production from CD4+ T, CD8+ T and Mucosal Associated Invariant T cells (MAITs). Results: 12 (4.3%) of TB patients were found to have FluA or FluB viral RNA present in their sputum at the time of TB diagnosis. The TB/Flu co-infected patients had a significantly higher bacterial load compared to those with TB mono-infection (p=0.0026). They had lower levels of IL17A in ex vivo sputum (p=0.0275) and higher MCP-1 (CCL2) levels in the blood following PPD stimulation (p=0.0267). TB/Flu co-infected subjects had significantly higher IFN-γ+IL-17+CD4+ and IFN-γ+IL-17-CD8+ cells compared to TB mono-infected subjects. Conclusions: These data show that Flu co-infection at time of TB diagnosis is associated with a higher bacterial load and differential cellular and soluble profiles. These findings show for the first time the impact of TB/Flu co-infection in a human cohort and support the potential benefit of Flu vaccination in TB-endemic settings.